2023
DOI: 10.1002/advs.202300726
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Perspectives on Supported Catalysts for Heterogeneous Hydrogen Production from Ammonia Borane

Abstract: Ammonia borane (AB), a liquid hydrogen storage material, has attracted increasing attention for hydrogen utilization because of its high hydrogen content. However, the slow kinetics of AB hydrolysis and the indefinite catalytic mechanism remain significant problems for its large-scale practical application. Thus, the development of efficient AB hydrolysis catalysts and the determination of their catalytic mechanisms are significant and urgent. A summary of the preparation process and structural characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 323 publications
0
25
0
Order By: Relevance
“…The intrinsic catalytic performance of CuNi alloys has been extensively demonstrated to surpass that of their respective pure metals in various reactions. 27–30 Also, the RWGS reaction as a model reaction can directly convert CO 2 into CO to further synthesise various value-added chemicals. 31–34 Combined with computational fluid dynamics (CFD) for gas flow behaviours, we demonstrated that the monolithic catalyst with a TPMS architecture exhibits significantly improved mass and heat transfer compared with the monolithic catalyst with a honeycomb structures.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic catalytic performance of CuNi alloys has been extensively demonstrated to surpass that of their respective pure metals in various reactions. 27–30 Also, the RWGS reaction as a model reaction can directly convert CO 2 into CO to further synthesise various value-added chemicals. 31–34 Combined with computational fluid dynamics (CFD) for gas flow behaviours, we demonstrated that the monolithic catalyst with a TPMS architecture exhibits significantly improved mass and heat transfer compared with the monolithic catalyst with a honeycomb structures.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen (H 2 ) is considered a green and efficient energy carrier, but efficient and controllable hydrogen storage remains a bottleneck for the future hydrogen economy. 37–40 Formic acid (FA, HCOOH) has emerged as a promising liquid-phase hydrogen storage material for portable H 2 storage applications. 41–44 In addition, FA can also be used as a green and cost-effective reductant for the reduction of toxic pollutants, such as hexavalent chromium (Cr( vi )), which possesses serious mutagenicity and carcinogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…8 Over the last five years, the ammonia–borane (NH 3 BH 3 , AB) complex has attracted significant attention in applications of hydrogen storage and chemical conversion. 9 AB is a potentially efficient, relatively cheap, easy-to-use/handle reagent and the hydrogenation is carried out employing standard glassware for transfer hydrogenation reactions. Furthermore, the major benefits of AB are it being air-stable under ambient conditions, of high hydrogen content (19.6 wt%, 152.8 gH 2 per L in theory), soluble in water and other polar solvents, less toxic, and widely accessible.…”
mentioning
confidence: 99%
“…Furthermore, the major benefits of AB are it being air-stable under ambient conditions, of high hydrogen content (19.6 wt%, 152.8 gH 2 per L in theory), soluble in water and other polar solvents, less toxic, and widely accessible. 9 Furthermore, hydrogen generation from AB has been investigated a lot by numerous researchers and hydrogen gas can be released straightforwardly by thermolysis or hydrolysis processes. 9 For these reasons, the utilization of AB as a hydrogen source in a variety of transfer hydrogenation reactions either in the presence of catalysts or catalyst-free systems has become successful.…”
mentioning
confidence: 99%
See 1 more Smart Citation